Comparison of Preeclampsia Rates in Pregnant Women with Mild vs. Moderate-to-Severe Systemic Lupus Erythematosus - Permana, Sandi Putra; Adrianes, Muhammad Bachnas; Aryoseto, Lukman; Yuliantara, Eric (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Preeclampsia is one of the leading causes of maternal mortality in Indonesia and is often associated with autoimmune conditions, such as Systemic Lupus Erythematosus (SLE). Therefore, this study aimed to compare the proportion of preeclampsia in pregnant women with mild and moderate-severe SLE. Subjects and Method: This cross-sectional design conducted in RSUD Dr. Moewardi. The population consisted of pregnant women with SLE treated at RSUD Dr. Moewardi between 2021 and 2023. A total of 77 pregnant patients with SLE selected from this study. The dependent variable was preeclampsia. The independent variable was pregnant women with SLE. This study utilized tools and materials in the form of medical record data from the Obstetrics and Gynecology Department at Dr. Moewardi Hospital, Surakarta. Data were analyzed using bivariate analysis with SPSS software and Fisher’s exact test tests. Results: A total of 77 subjects who met the inclusion criteria. Subjects with moderate-severe degrees had preeclampsia 28.6% (n = 4). While subjects with mild degrees experienced preeclampsia 20.6% (n = 13). There was no significant relatoionship between the degree of systemic lupus erythematosus activity and preeclampsia (p = 0.496). Conclusion: This study showed no significant association between the degree of systemic lupus erythematosus activity and preeclampsia.